Distinct Seasonal Patterns of Bacterioplankton Abundance and Dominance of Phyla α-Proteobacteria and Cyanobacteria in Qinhuangdao Coastal Waters Off the Bohai Sea - He, Yaodong; Sen, Biswarup; Zhou, Shuangyan; Xie, Ningdong; Zhang, Yongfeng; Zhang, Jianle; Wang, Guangyi (Frontiers in Microbiology, 2017)
Qinhuangdao coastal waters in northern China are heavily impacted by anthropogenic and natural activities, and we anticipate a direct influence of the impact on the bacterioplankton abundance and diversity inhabiting the adjacent coastal areas. To ascertain the anthropogenic influences, we first evaluated the seasonal abundance patterns and diversity of bacterioplankton in the coastal areas with varied levels of natural and anthropogenic activities and then analyzed the environmental factors which influenced the abundance patterns. Results indicated distinct patterns in bacterioplankton abundance across the warm and cold seasons in all stations. Total bacterial abundance in the stations ranged from 8.67x104 to 2.08x106 cells/mL and had significant (p<0.01) positive correlation with total phosphorus (TP), which indicated TP as the key monitoring parameter for anthropogenic impact on nutrients cycling. Proteobacteria and Cyanobacteria were the most abundant phyla in the Qinhuangdao coastal waters. Redundancy analysis revealed significant (p<0.01) influence of temperature, dissolved oxygen and chlorophyll a on the spatiotemporal abundance patterns of -Proteobacteria and Cyanobacteria groups. Among the 19 identified bacterioplankton classes, -Proteobacteria (phylum Proteobacteria) was the dominant class followed by Family II (phylum Cyanobacteria), representing 19.1¬55.2% and 2.354.2% of total sequences, respectively. An inverse relationship (r = -0.82) obeying the competitive exclusion principle was observed between the two dominant heterotrophic classes, -Proteobacteria and Family II, which signifies their utilization of similar nutrient resources. A wide range of inverse Simpson index (10.2 to 105) revealed spatial heterogeneity of bacterioplankton diversity resulting from varied anthropogenic and natural influences. Overall, our results suggested seasonal variations impose substantial influence on shaping bacterioplankton abundance patterns, while the spatial variation of diversity in a season seemed largely due to undefined factors. In addition, the predominance of only a few cosmopolitan species in the Qinhuangdao coastal wasters is probably an indication of selective advantage of these species to overcome the load of chemical inputs for degradation. This provides evidence for their ecological significance at seasonally driven natural- and anthropogenic-inputs impacted coastal habitats. In conclusion, the findings anticipate future development of effective indicators of coastal health monitoring and subsequent management strategies to control the anthropogenic inputs at the Qinhuangdao coastal areas.